Optimization of milling parameters to improve the surface roughness using the taguchi methodology - Blanca, Alberto (2015)
This paper presents a study of Taguchi design application to optimize surface quality in a CNC milling operation. Maintaining good surface quality usually involves additional manufacturing cost or loss of productivity. The Taguchi design is an efficient and effective experimental method in which a response variable can be optimized, given various control and/or noise factors, using fewer resources than a factorial design. This study includes feed per tooth, cutting speed and radial depth of cut as control factors. An orthogonal array of L9(34) was implemented and the ANOVA analyses were carried out to identify the significant factors affecting surface roughness as well as the determination of optimal cutting combination by seeking the best surface roughness (response) and signal-to-noise ratio.